Pemanfaatan Dana Kapitasi oleh Puskesmas di Kota Lubuklinggau Tahun 2014-2016 - Muhammad Yulianto, Muhammad Muhammad Yulianto; Nadjib, Mardiati (UI Scholars Hub, 2017)
Since the implementationof National Health Insurance (JKN), Health Centers received the payment from Social Security Agency for Health (BPJS) using capitation. In Lubuklinggau City, there has been problem inutilizing capitation and financing surplus (SiLPA) for approximately 23% per year. This research aimed to analyze the utilization of capitationin Lubuklinggau City 2014-2016. This qualitative study was implemented in SimpangPeriuk Health Center, Taba, Citra Medika and Swasti Saba which werethe lowest and highest SiLPA absorption, and data were collected retrospectively. The study revealedthat the capitation funds have achieved the target (69,5%) while spending for operational was still under utilized (12,4%). The planning for using capitation funds was not systematically implemented using appropriate steps : Planning, Organazing, Actuating, Controlling. Health centers assumed thatthe regulationto use the funds was too complicated to follow so they could not absorp the capitation appropriately. Monitoring assitance are needed to improve the absorption of capitation funds.